Anti-inflammatory effects of locally applied enzyme-loaded ultradeformable vesicles on an acute cutaneous model - Simoes, Sandra (2015)
Superoxide dismutase (SOD) and catalase (CAT) are active scavengers of reactive oxygen species and were incorporated into ultradeformable vesicles with the aim of increasing enzyme bioavailability (skin delivery). These special very adaptable vesicles have been formulated and optimized for enzyme transport in order to penetrate into or across the intact skin barrier. Anti-inflammatory activity of SOD-loaded, CAT-loaded and of SOD- and CAT-loaded ultradeformable vesicles applied epicutaneously was measured using different protein doses on the skin, on an arachidonic acid-induced mouse ear oedema. The biological anti-oedema activity is a measurement of drug-targeting potentiation in the organ. Delivery by means of deformable vesicles was compared to conventional vesicles or the absence of an enzyme carrier mediated transport. This was done at various times following prophylactic application of the test formulations. Positive reference groups were treated epicutaneously with several low molecular weight non-steroidal anti-inflammatory drugs (NSAIDs). The latter included indomethacin (3 mg kg(-1)), etofenamate (30 mg kg(-1)) and piroxicam (11 mg kg(-1)) and reduced the oedema by 94 +/- 4%, 81 +/- 4% and 42 +/- 5%, respectively, if measured 30 min after ear treatment with a NSAID. Of the enzyme-loaded carriers tested, only the enzyme-loaded ultradeformable vesicles reduced the swelling of ears significantly: SOD (90 mu g kg(-1)), CAT (250 mu g kg(-1)) and SOD (90 mu g kg(-1)) plus CAT (250 mu g kg(-1)) reduced the oedema by 70 +/- 12%, 65 +/- 10% and 61 +/- 19%, respectively, at t = 30 min. Aqueous enzyme solutions and empty carriers had no such effect. The combination of two enzymes resulted in no increased therapeutic effect, but the results are inconclusive since only two dose combinations were tested. The results presented in this study suggest that antioxidant enzymes delivered by means of ultradeformable lipid vesicles can serve as a novel region-specific treatment of inflammation.. - Fundacao para a Ciencia e para a Tecnologia [POCTI/1999/FCB/35787]. - Professor Gregor Cevc is acknowledged for the discussion of the results. The work was financially supported by Fundacao para a Ciencia e para a Tecnologia, project POCTI/1999/FCB/35787.